Cafeteria Diet Impacts the Body Weight and Energy Expenditure of Brown Norway Rats in an Apparent Age Dependent Manner, but Has no Effect on Muscle Anabolic Sensitivity to Nutrition - El Ayadi, Amina; Tapking, Christian; Prasai, Anesh; Rontoyanni, Victoria G.; Abdelrahman, Doaa R.; Cui, Weihua; Fang, Geping; Bhattarai, Nisha; Murton, Andrew J. (Frontiers in Nutrition, 2021)
While obesity blunts the ability of muscle to mount a protein synthetic response to an amino acid infusion in older adults, it is unclear if this insensitivity to nutrition persists long term and in response to complete foods is unknown. To address this, young (2 months old) and old (17–20 months old) Brown Norway rats were randomized to receive either chow or a 12 wk diet of calorie-dense human foods. At wk 10 drinking water was supplemented with 2% heavy water, followed 2 weeks later by a flooding dose of [2H5]-phenylalanine and an oral leucine bolus, allowing the short and long-term effects of age and diet on muscle protein synthesis rates to be determined. The experimental diet increased energy intake in both young (7.4 ± 0.9%) and old (18.2 ± 1.8%) animals (P < 0.01), but only led to significant increases in body weight in the former (young: 10.2 ± 3.0% (P < 0.05) and old: 3.1 ± 5.1% (NS) vs. age-matched controls). Notably, energy expenditure in response to the cafeteria diet was increased in old animals only (chow: 5.1 ± 0.4; cafe: 8.2 ± 1.6 kcal.kg b.w−1.h−1; P < 0.05). Gastrocnemius protein fractional synthetic rates in response to either an acute leucine bolus or two weeks of feeding were equivalent across groups irrespective of age or diet. Rodents in old age appear capable of preventing weight gain in response to a calorie-dense diet by increasing energy expenditure while maintaining the anabolic sensitivity of muscle to nutrition; the mechanisms of which could have important implications for the aging obese human.